HOME-SCHOOL COLLABORATION STRATEGY FOR EFFECTIVE LEARNING IN PRE-PRIMARY AND PRIMARY SCHOOLS IN AWKA SOUTH LGA OF ANAMBRA STATE - Nweke, Maryann C.; Anyachebelu, Faith E.; Mbachi, Roseline A. (Journal of Early Childhood and Primary Education, 2020)
This study examined home-school collaboration: strategies for effective learning in pre-primary and primary schools in Awka South LGA of Anambra state. The study was guided by two research questions. It adopted descriptive survey research design. The population comprised of 3783 pre-primary and primary school parents in Awka South L.G.A. Simple random sampling was employed to select 40 pre-primary school parents and 110 primary school parents from 15 pre-primary and primary school selected for this study, making a total of 150 parents selected for the study. Instrument for data collection in this study was a structured questionnaire with 17 items titled ‘Home-School Collaboration Questionnaire’ (HSCQ) for parents. The instrument was validated by three experts. Cronbach Alpha was to determine the reliability of the instrument and the overall reliability of 0.71 was obtained. Mean was used to analyze the research questions. The findings from the study revealed that Home-school collaboration through homework completion, teaches pupils to work independently and develop self-discipline among others are ways parents involve themselves in the education of their children in pre- primary and primary schools. Findings also revealed that project enhances learning among pupils and that project based learning provides pupils with opportunities to drive home their own learning among others are the strategies parents and teachers use for effective learning in pre-primary and primary schools. Based on the above findings, it was recommended among others that school heads should encourage home-school collaboration in pre-primary, primary schools to give parents opportunities to contribute to the education of their children.